Comparison of Serum Magnesium and Potassium in Acute Myocardial Infarction and Chronic Ischemic Heart Disease - Choudhury, MBK; Rahman, MS; Hassan, MM; Begum, R; Hoque, N; Akhtaruzzaman, M; Chowdhury, AN (Journal of Dhaka National Medical College & Hospital, 2012)
The comparative study has been designed to estimate serum magnesium (Mg) and potassium (K) in patients with acute myocardial infarction (AMI) and chronic ischemic heart disease (CIHD). A total 61 subjects were selected and were divided as group-I (30 subjects of AMI) and group-II (31 subjects of CIHD). Laboratory investigations were done for estimation of serum glucose and serum creatinine to exclude the diabetes mellitus and renal disease. Serum Mg was estimated by atomic absorption spectrophotometer and serum K by ion selective electrode. This study showed that Mg and K level in serum is significantly lower in patients with AMI than that of CIHD subjects. Findings of the study suggested that significantly reduced serum level of Mg and K persists in AMI than those of CIHD, which may be the cause of further cardiac complications. So it may be recommended for estimation and supplementation of Mg and K in both the cases of AMI and CIHD patients for better management. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12190 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 33-36